2017
DOI: 10.1192/bjp.bp.117.205955
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and psychotic experiences: transnational data from the World Mental Health Survey

Abstract: Background Traumatic events are associated with increased risk of psychotic experiences, but it is unclear whether this association is explained by mental disorders prior to psychotic experience onset. Aims To investigate the associations between traumatic events and subsequent psychotic experience onset after adjusting for post-traumatic stress disorder and other mental disorders. Method We assessed 29 traumatic event types and psychotic experiences from the World Mental Health surveys and examined the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 24 publications
4
68
0
Order By: Relevance
“…The age range of studies in the GP was quite wide (9.8-51.7 years), and thus the population included in these studies is quite heterogeneous as Psychological Medicine different confounding factors may operate at different ages; this should be considered as a limitation when interpreting our results. Furthermore, only three papers took into account different mediating effects based on the timing of adversity (McDonnell et al, 2018;Schalinski et al, 2019;Wolke et al, 2014) which is an important limitation of current research as different mediating mechanisms may operate differently based on the developmental period (McGrath et al, 2017). Lastly, there was a time lag between the systematic literature search, in July 2019, and the submission date in February 2020, which means newer studies were not included in the current work.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The age range of studies in the GP was quite wide (9.8-51.7 years), and thus the population included in these studies is quite heterogeneous as Psychological Medicine different confounding factors may operate at different ages; this should be considered as a limitation when interpreting our results. Furthermore, only three papers took into account different mediating effects based on the timing of adversity (McDonnell et al, 2018;Schalinski et al, 2019;Wolke et al, 2014) which is an important limitation of current research as different mediating mechanisms may operate differently based on the developmental period (McGrath et al, 2017). Lastly, there was a time lag between the systematic literature search, in July 2019, and the submission date in February 2020, which means newer studies were not included in the current work.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Childhood maltreatment is implicated in the development of a range of adult psychopathology crossing diagnostic categories (Kessler et al ., ; Vachon, Krueger, Rogosch, & Cicchetti, ; van Nierop et al ., ), including psychotic disorders (Green, Girshkin, Teroganova, & Quidé, ; Hardy et al ., ; Read, Fosse, Moskowitz, & Perry, ; Varese et al ., ). Meta‐analytic studies suggest a twofold to threefold increase in risk for psychotic disorders in those with a history of childhood maltreatment (Matheson, Shepherd, Pinchbeck, Laurens, & Carr, ; McGrath et al ., ; Varese et al ., ). While sexual abuse alone has been reported as a significant risk factor for psychotic symptoms (Cutajar et al ., ), no particular type of trauma has been consistently implicated as a stronger predictor of psychotic symptoms relative to any other (Varese et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, no effect on PLEs was found in a 20 year follow-up study on PLEs in individuals affected by bushfires in Australia (30). Data from the World Mental Health survey confirmed a weak effect of natural disaster of unspecified type on PLEs, that did not hold after controlling for confounders (2).…”
Section: Comparison With Previous Literaturementioning
confidence: 90%
“…On the other hand, natural disasters affect the incidence of several mental disorders (10); however, their relevance as risk factors for PLEs is controversial. Natural disasters showed a weak effect on PLEs rate compared to interpersonal traumatic events in a large international study (2). Local studies have found opposite results (11,12).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation